Telaah Kritis Terhadap Perkawinan Usia Muda Menurut Hukum Islam - Moh. Ali Wafa (Universitas Islam Negeri Jakarta, 2017)
Young marriage discourse has always been a debate in Islamic legal thought. This study analyzes differences of opinion among jurists in determiningage limits (balīgh, iḥtilām, rushd) which implicates the right of ijbār in marriage.The scholars of Shafiyah allow the right of ijbār with very difficult and rigid requirements, while Ibn Shubrumah, Abu Bakr, Al-A'sham and Al-Batii do not allow the right of ijbār, even their marriages are considered null and legal. This study found that marriage of young age is determined by the benefits arising from marriage. This study has implications for the implementation of the maslahah mursalah as an alternative in establishing the law on the age limit of marriage in Indonesia. DOI: 10.15408/ajis.v17i2.6232